Evaluating the Impact of Leader-Member Exchange (LMX) Theory on the Interactions Between Managers and Employees in Chosen Ghanaian Banking Institutions - Sulemana, Iddrisu; Bawah, Mohammed; Sadiq, Mohammed Abubakari (International Journal of Membrane Science and Technology, 2023)
Purpose - The objective of this study is to explore how employee results, including job performance and job contentment, are linked to evaluations made by both employees and managers concerning the caliber of. the leader-member relationship (referred to as LMX). Design/Methodology/Approach – A correlational design and descriptive survey method were employed to collect data through a questionnaire administered to both superiors and their subordinates. The study utilized data from 10 banks to test the hypothesis. Findings: The study revealed a moderate link in relation to the exchanges within leader-member relationships and their impact on employee job performance. The investigation identified a minor but positive association between the motivation of employees and the efficacy of interactions between leaders and subordinates. The gender of leaders did not notably affect the caliber of interactions between leaders and followers.